Pengembangan Media Pembelajaran Berbasis Microsite pada Pembelajaran Pemesanan dan Penghitungan Tarif Penerbangan SMK Usaha Perjalanan Wisata - Bayu Prisa Setia Adi; Atiqoh Atiqoh; Hari Karyono (Jurnal Pendidikan : Riset dan Konseptual, 2023)
So far, learning the competency of ordering and calculating flight fares still uses the conventional method where fares have been determined and use public fares that have been attached to applications intended for direct consumers. This is certainly less effective and efficient in today's digital era. This research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model aims to develop interactive learning media based on Microsite in learning Booking and Calculating Flight Fare for students of class XI Travel Business at SMK Negeri 2 Blitar. The results showed that: a) the design expert's assessment with a percentage of 95% with very good criteria and declared suitable for use, the results of the media expert's assessment with a percentage of 88.42% with very good criteria and declared suitable for use, b) the results of the material expert's assessment with a percentage of 95% with very good criteria and declared suitable for use, and respondents' ratings obtained a percentage of 86.99% with very good criteria and declared suitable for use. Thus, it can be concluded that Microsite-based interactive learning media consists of three aspects of development, namely design, media, and materials. The feasibility of microsite-based interactive learning media from the validation results of a team of design experts, media, and materials is very attractive to students and is suitable for use as a support for learning resources for vocational students in the competency skills of the Travel and Tourism Business.